Enhancing Financial Sector Surveillance in Low-Income Countries : Case Studies. (Policy Papers; Policy Paper, 2012)
This supplement presents ten case studies, which highlight the roles of targeted policies to facilitate sustainable financial deepening in a variety of country circumstances, reflecting historical experiences that parallel a range of markets in LICs. The case studies were selected to broadly capture efforts by countries to increase reach (e.g., financial inclusion), depth (e.g., financial intermediation), and breadth of financial systems (e.g., capital market, cross-border development). The analysis in the case studies highlights the importance of a balanced approach to financial deepening. A stable macroeconomic environment is vital to instill consumer, institutional, and investor confidence necessary to encourage financial market activity. Targeted public policy initiatives (e.g., collateral, payment systems development) can be helpful in removing impediments and creating infrastructure for improved market operations, while ensuring appropriate oversight and regulation of financial markets, to address potential sources of instability and market failures.a.